Editorial: opioids in inflammatory bowel disease—primum non nocere. Authors' reply. Issue 7 (11th March 2021) - Rhudy, Christian; Perry, Courtney L.; Barrett, Terrence A.
Abstract : LINKED CONTENT This article is linked to Rhudy et al and van der Have & Maljaars papers. To view these articles, visit https://doi.org/10.1111/apt.16269 and https://doi.org/10.1111/apt.16286